Productivity and Firm Boundaries - Wilhelm Kohler; Marcel Smolka (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper develops and applies a test of the property rights theory of the firm in the context of global input sourcing. We use the model by Pol Antràs and Elhanan Helpman, “Global Sourcing," Journal of Political Economy, 112:3 (2004), 552-80, to derive a new prediction regarding how the productivity of a firm affects its choice between vertical integration and outsourcing and how this effect depends on the relative input intensity of the production process. The prediction we derive hinges on less restrictive assumptions than industry-level predictions available in existing literature and survives in more realistic versions of the model featuring multiple suppliers and partial vertical integration. We present robust firm-level evidence from Spain showing that, in line with our prediction, the effect of productivity works more strongly in favor of vertical integration, and against outsourcing, in more headquarter-intensive industries.
Keywords: F12; F19; F23; L22; L23; 330; global sourcing; incomplete contracts; property rights theory; firm productivity